2009
DOI: 10.1080/17470210902973106
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the online processing of counterfactual and indicative conditionals

Abstract: The ability to represent conditional information is central to human cognition. In two self-paced reading experiments we investigated how readers process counterfactual conditionals (e.g., If Darren had been athletic, he could probably have played on the rugby team) and indicative conditionals (e.g., If Darren is athletic, he probably plays on the rugby team). In Experiment 1 we focused on how readers process counterfactual conditional sentences. We found that processing of the antecedent of counterfactual con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 15 publications
1
42
0
3
Order By: Relevance
“…Another factor that may have contributed to the divergence between our results and those of Ferguson colleagues could be the type of counterfactual materials that were used. Alternative endings to known historical events may be relatively easily computed, for example because relevant information is also part of our real-world knowledge (e.g., of the 'Space Race' and the fact that the Soviets 2 Differences in contextual constraint may have been exacerbated by the fact that our manipulation occurred in a counterfactual condition sentence whereras earlier studies on counterfactual comprehension have looked at later effects (but see Stewart, Haigh, & Kidd, 2009). However, we do not know of any principled reason why there should be differences between counterfactual sentence and discourse manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may have contributed to the divergence between our results and those of Ferguson colleagues could be the type of counterfactual materials that were used. Alternative endings to known historical events may be relatively easily computed, for example because relevant information is also part of our real-world knowledge (e.g., of the 'Space Race' and the fact that the Soviets 2 Differences in contextual constraint may have been exacerbated by the fact that our manipulation occurred in a counterfactual condition sentence whereras earlier studies on counterfactual comprehension have looked at later effects (but see Stewart, Haigh, & Kidd, 2009). However, we do not know of any principled reason why there should be differences between counterfactual sentence and discourse manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have looked at counterfactual language comprehension using online measures (de Vega, Urrutia, & Riffo, 2007;Ferguson, 2012;Ferguson, Scheepers, & Sanford, 2010;Nieuwland & Martin, 2012;Stewart, Haigh, & Kidd, 2009;Urrutia, de Vega, & Bastiaansen, 2012). showed that despite a counterfactual context (e.g., ''If cats were vegetarians'') sentences describing implausible real-world events (e.g., ''Families would feed their cat a bowl of carrots'') incurred brief disruptions during reading (i.e., longer early fixations in eye-tracking; see also , for N400 evidence), suggesting that counterfactual context came into play after realworld constraints had their effect (see Ferguson, Sanford, & Leuthold, 2007, on the role of negation).…”
mentioning
confidence: 99%
“…La mayoría de los estudios, como los que hemos revisado en el apartado anterior, concluyen que se activan dos modelos mentales en la comprensión de un contrafactual (Johnson-Laird y Byrne 2002; y Santamaría et al 2005. No obstante, en un trabajo reciente se intentó aportar datos a favor de la teoría suposicional (Stewart et al 2009). En dicha investigación, que describiremos en detalle en la próxima sección, los autores, mediante una tarea de lectura autoespaciada palabra por palabra, hallaron evidencia favorable a la teoría suposicional sólo cuando los participantes leían condicionales indicativos ("Si Darren es atlético, probablemente jugará en el equipo de rugby"), pero no en los condicionales contrafactuales ("Si Darren hubiera sido atlético, probablemente habría jugado en el equipo de rugby"), por tanto los resultados falsean más que confirman la teoría de Evans.…”
Section: Teoría Suposicionalunclassified